Impaired oligodendroglial turnover is associated with myelin pathology in focal cortical dysplasia and tuberous sclerosis complex. (9th February 2017) - Scholl, Theresa; Mühlebner, Angelika; Ricken, Gerda; Gruber, Victoria; Fabing, Anna; Samueli, Sharon; Gröppel, Gudrun; Dorfer, Christian; Czech, Thomas; Hainfellner, Johannes A.; Prabowo, Avanita S.; Reinten, Roy J.; et al.
Abstract: Conventional antiepileptic drugs suppress the excessive firing of neurons during seizures. In drug‐resistant patients, treatment failure indicates an alternative important epileptogenic trigger. Two epilepsy‐associated pathologies show myelin deficiencies in seizure‐related brain regions: Focal Cortical Dysplasia IIB (FCD) and cortical tubers in Tuberous Sclerosis Complex (TSC). Studies uncovering white matter‐pathology mechanisms are therefore urgently needed to gain more insight into epileptogenesis, the propensity to maintain seizures, and their associated comorbidities such as cognitive defects. We analyzed epilepsy surgery specimens of FCD IIB ( n  = 22), TSC ( n  = 8), and other malformations of cortical development MCD ( n  = 12), and compared them to autopsy and biopsy cases ( n  = 15). The entire lesional pathology was assessed using digital immunohistochemistry, immunofluorescence and western blotting for oligodendroglial lineage, myelin and mTOR markers, and findings were correlated to clinical parameters. White matter pathology with depleted myelin and oligodendroglia were found in 50% of FCD IIB and 62% of TSC cases. Other MCDs had either a normal content or even showed reactive oligodendrolial hyperplasia. Furthermore, myelin deficiency was associated with increased mTOR expression and the lower amount of oligodendroglia was linked with their precursor cells (PDGFRa). The relative duration of epilepsy (normalized to age) also correlated positively to mTOR activation and negatively to myelination. Decreased content of oligodendroglia and missing precursor cells indicated insufficient oligodendroglial development, probably mediated by mTOR, which may ultimately lead to severe myelin loss. In terms of disease management, an early and targeted treatment could restore normal myelin development and, therefore, alter seizure threshold and improve cognitive outcome.